PENGENALAN PEMBIAYAAN SYARIAH DALAM PEMULIHAN USAHA MIKRO KECIL DAN MENENGAH MELALUI PROGRAM BANTUAN PRODUKTIF USAHA MIKRO PADA MASA PANDEMI COVID-19 DI DESA CIASMARA, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Ria Kusumaningrum; Abdul Kodir; Fika Fitria Ningsih (SAHID DEVELOPMENT JOURNAL, 2022)
The role of Micro, Small and Medium Enterprises (MSMEs) is very important in building an economy based on a just economic democracy. Like most business entities, MSMEs have been heavily influenced by uncertain market conditions since the Covid-19 pandemic. However, MSMEs with less stringent capital characteristics and regulations have relatively good resilience and flexibility to deal with a pandemic situation. However, there are also MSMEs that lack the resilience and flexibility to deal with a pandemic due to low levels of digitization, difficulty accessing technology, and a lack of understanding of strategies to survive in business. This also happened in Ciasmara Village, Pamijahan District, Bogor Regency. The government has also carried out programs to maintain the sustainability of MSMEs in the midst of a pandemic. One of the government's programs to maintain the existence of MSMEs during the Covid-19 pandemic, by conducting MSME Productive Assistance (BPUM). Simultaneously with the implementation of government programs that directly support these MSMEs, community service was also carried out in Ciasmara Village, Pamijahan District, Bogor Regency. Thus, in addition to having BPUM from the government, there is also the introduction of sharia financing as part of community service activities in Ciasmara Village, Pamijahan District, Bogor Regency.